ANALISIS PEMASARAN KOPI ARABIKA DI DESA BELANTIH KECAMATAN KINTAMANI KABUPATEN BANGLI - Egristofer Evander Tuar; I Made Tamba; Putu Fajar Kartika Lestari (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2019)
Indonesia is a country that has an advantage in plantation commodity trading. One such commodity is arabica coffee. This study aims to identify marketing channels and the magnitude of Arabica coffee marketing margins. The basic method used is the descriptive method. Determination of the location of the study was chosen deliberately. Sampling of farmers was selected by means of Slovin. The time and location of the study are in Belantih Village, Kintamani District, Bangli Regency, this research took place from 15 May to 20 July 2019. The population in this study amounted to 118 and sampled 55. Based on the results of the study, there was one marketing channel of Arabica coffee in the study site, namely: farmers - collectors - large traders while the marketing margin in the marketing channel is Rp. 28,000 per kilogram.